2002
DOI: 10.3354/meps234015
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore-mediated increase in the photosynthetic capacity of marine biofilms: indirect effects of changing microalgal assemblage composition

Abstract: The effects of grazing by the high-shore periwinkle Nodilittorina africana on the biomass, productivity, composition and diversity of microalgal assemblages were experimentally assessed on the south coast of South Africa. The results indicate that littorinids selectively removed large/filamentous and loosely attached 'overstorey' cyanobacteria, thereby reducing microalgal biomass and species diversity. As grazers also eliminated macroalgal sporelings, they restricted the upper distributional limit of Ulva spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
1
28
2
Order By: Relevance
“…However, never-grazed areas did have proportionally more filamentous cyanobacteria, while grazed areas had more coccoid cyanobacteria and lichen. Cell chains and filamentous growth forms are generally absent from grazed biofilms because larger and filamentous taxa are more easily removed by grazers (Nicotri 1977, Norton et al 1990, Kaehler & Froneman 2002. Studies from a wide range of macrophytic systems have likewise found that community responses to grazing are associated with plant growth form (Noy-Meir et al 1989, Huntly 1991.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, never-grazed areas did have proportionally more filamentous cyanobacteria, while grazed areas had more coccoid cyanobacteria and lichen. Cell chains and filamentous growth forms are generally absent from grazed biofilms because larger and filamentous taxa are more easily removed by grazers (Nicotri 1977, Norton et al 1990, Kaehler & Froneman 2002. Studies from a wide range of macrophytic systems have likewise found that community responses to grazing are associated with plant growth form (Noy-Meir et al 1989, Huntly 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of grazing history was still evident at termination of the experiment, 7 mo after snail removal, suggesting an enduring effect of grazing. Painter et al (1993) found the effect of prairie dog and Evidence of grazing history is typically ascribed to grazer-instigated shifts in the composition or structural organisation of plant communities (Kaehler & Froneman 2002, McIntire & Hik 2005. The biofilm community could not be sampled in ungrazed halos because of the destructive nature of SEM and HPLC, and therefore we cannot know how the community responded to snail removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variety of types of EMPB can be greatest in summer (MacLulich 1987). Other studies have investigated how the composition of EMPB is affected by grazing (Nicotri 1977, Hawkins et al 1989, Kaehler & Froneman 2002, grazing history (Skov et al 2010), or succession (MacLulich 1986 To understand the consequences of different temperatures and exposures to waves, we used field spectrometry to estimate distributions, amounts and types of EMPB over 2 yr for different seasons, exposures to waves and heights on the shore, in a warm temperate area (Sydney) and in a subtropical area (Brisbane) . We predicted: (1) greater biomass of the EMPB in Sydney than in Brisbane; (2) more algae during cool than during warm seasons; (3) more EMPB lower than higher on the shore; and (4) that effects of latitude, season, exposure to waves and height on the shore would interact to influence biomass of EMPB.…”
Section: Introductionmentioning
confidence: 99%
“…The grazing effect of the larger size classes (macrofauna such as gastropods, insect larvae, herbivorous fish, mayflies) on biomass, diversity, composition, heterogeneity and production of microalgal biofilms has previously been investigated (Liess & Hillebrand 2004, Alvarez & Peckarsky 2005. It is known that macrograzers such as gastropods may stimulate production of attached microalgal communities (Kaehler & Froneman 2002). In contrast, previous studies of the effect of smaller metazoans (meiofauna) are rare.…”
Section: Introductionmentioning
confidence: 99%